1984
DOI: 10.1007/bf00507060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic naloxone treatment on development of hypertension in the spontaneously hypertensive rat

Abstract: Chronic administration of naloxone by means of miniosmotic pumps retarded the development of hypertension in young spontaneously hypertensive rats (SHRs) in a dose-related manner. Abrupt termination of naloxone treatment resulted in acceleration in the rate of the blood pressure increase, while increasing the naloxone concentration further slowed the development of hypertension in SHRs. The heart rates of SHRs undergoing chronic naloxone treatment were generally lower than those of control SHRs. Naloxone had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…49 - 12 In part, this may be due to the possibility that endogenous opioid systems remain silent until activated by specific stimuli. In this manner, the arterial hypotension of endotoxic, circulatory, and hemorrhagic shock have been shown to be antagonized by blockade of opioid receptors with naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…49 - 12 In part, this may be due to the possibility that endogenous opioid systems remain silent until activated by specific stimuli. In this manner, the arterial hypotension of endotoxic, circulatory, and hemorrhagic shock have been shown to be antagonized by blockade of opioid receptors with naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory Systems An interesting question regarding pain and cardiovascular regulatory systems relates to the functional organization that supports this interaction. At least two schemes based on existing anatomical, physiological, and behavioral evidence (Randich and Maixner, 1984[a]; Smith and DeVito, 1984;Janig, 1985;Randich and Aicher, 1988;Loewy, 1990) can be proposed. Tbe first scheme is based on that predicted by Cannon's (1927Cannon's ( , 1939 thalamic theory of emotions.…”
Section: Organizational Schemes Supporting An Interaction Between Carmentioning
confidence: 99%
“…In general, in experimental studies brain opioid systems were reported to exert hypertensive or hypotensive influence via stimulation or inhibition of central sympathetic output, the effect depending on the actual brain structures and the opioid receptor species involved (Appel et al 1986;Siren and Feuerstein 1992). For instance, one early study suggested that enhancement by morphine of Ang II dependent pressor effects was mediated by stimulation of circumventricular organs (probably area postrema) (Shilagyi and Ferrario 1981), and chronic inhibition of opioid receptors with naloxone was reported to suppress the development of hypertension in young SHR (Quock et al 1984). On the other hand, other workers did not find convincing evidence on the role of brain opioid systems in experimental hypertension (Sun et al 1996).…”
Section: Introductionmentioning
confidence: 97%